Estudo fitoquímico e atividade biológica de raízes de Maytenus imbricata Mart. ex. Reissek - Vanessa Gregório Rodrigues (2011)
This work described the phytochemical study of the hexane/diethyl ether (1:1) extract of the roots of Maytenus imbricata, and the evaluation of biological activity of extracts and isolated substances.The phytochemical study resulted in the isolation and characterization ofseven pentacyclic triterpenes, 11alpha-hydroxylup-20(29)-en-3-one, tingenone, 6-oxotingenol, 30-hydroxylup-20(29)-en-3-one, 3,7-dioxofriedelane, 3-oxo-29- hydroxyfriedelane and 3beta,11alpha-di-hydroxylup-20(29)-ene, as well as palmitic acid anda mixture of long chain hydrocarbons (C-27 to C-32). All substances had their structures elucidated by spectrometric methods (IR, 1H and 13C NMR) and gas chromatography. Tingenone, 6-oxo-tingenol, 3,7-dioxofriedelane, 3-oxo-29-hydroxyfriedelane, 3beta, 11alpha-di-hydroxylup-20(29)-ene, palmitic acid and the mixture of hydrocarbons were isolated by first time in M. imbricata. The compound 6-oxo-tingenol was for the first time isolated in NEPLAM and its structure was determined by 1D and 2D NMR. The extracts and some constituents were submitted to assays of antimicrobial activity (antibacterial and antifungical), inhibition property of the enzyme acethylcholinesterase, and evaluation of toxic potential through the larvicidal activity using Artemia salina. All extracts and 11alpha-hydroxylup-20(29)-en-3-one, tingenone and 6-oxotingenol showed activity against Staphylococcus aureus, Bacillus cereus, Salmonella typhimurium, Escherichia coli and Candida albicans. The mixture of triterpenes (11alpha- hydroxylup-20(29)-en-3-one + 30-hydroxylup--20(29)-en-3-one) was active against Staphylococcus aureus, Bacillus cereus and Candida albicans. In the evaluation of inhibition capacity of the enzyme acethylcholinesterase by the bioautography method, the constituents 1alpha- hydroxylup-20(29)-en-3-one, 3,7- dioxofriedelan and 3-oxo-29-hydroxyfriedelan were active. By the method using Artemia salina, all extracts and compounds tested showed potential larvicidal activity